2010
DOI: 10.1179/107735210800546326
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Surveillance of Informal Workers' Health in Two Cities in Southeastern Brazil

Abstract: Informal labor markets have grown in peripheral countries, accounting for more than 50% of jobs. There is anecdotal evidence of a direct relation between informal sector growth and an increase in the frequency and severity of work-related diseases and injuries. Two sister pilot projects were conducted in Uberaba and Campinas, Brazil to develop population-based epidemiological surveillance of workplace injuries in the informal sector. Results for Campinas and Uberaba found cumulative yearly incidences of 5.1% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Limited attention has been given to different occupational hazards related to different sectors of informal work. 11–14 In informal workplaces, chemical hazards, dust, noise, and musculoskeletal disorder problems are commonly observed. 15 In the Americas, a review of the literature found an increased risk for minor mental disorders among women working informally, 11,16,17 particularly for young domestic workers and waste pickers, regardless of sex or age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited attention has been given to different occupational hazards related to different sectors of informal work. 11–14 In informal workplaces, chemical hazards, dust, noise, and musculoskeletal disorder problems are commonly observed. 15 In the Americas, a review of the literature found an increased risk for minor mental disorders among women working informally, 11,16,17 particularly for young domestic workers and waste pickers, regardless of sex or age.…”
Section: Introductionmentioning
confidence: 99%
“…20 In Brazil, several studies fail to show differences concerning fatal or nonfatal work injuries between informal and formal workers. 13,21 In contrast, findings from industrialized countries demonstrate that fatal and serious nonfatal injuries occur more often among workers holding precarious jobs than their counterparts. 2…”
Section: Introductionmentioning
confidence: 99%